2017
DOI: 10.32412/pjohns.v32i1.171
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Perforation of the Tympanic Membrane: Etiologies and Risk Factors for Healing and Intervention

Abstract: Objective: To study various etiologies of traumatic tympanic membrane perforation; evaluate the factors involved in healing of traumatic tympanic membrane perforation; and identify patients with perforations unlikely to benefit from conservative management. Methods Study Design:  Prospective observational study Setting:            Tertiary Government Medical College and Hospital Subjects:          64 consecutive cases of traumatic tympanic membrane perforation seen over one year were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…p=0.000), that is supported by study of Sannigrahi who found significant association between mode of injury and tympanic membrane perforation after three months (χ2 = 23.30; p = .00001). 13 Another study results also showed that there was statistically significant difference between TM perforation and age of the patient, severity of deafness, size of perforation (p <0.05) as shown. 8 Fazal I Wahid et al…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…p=0.000), that is supported by study of Sannigrahi who found significant association between mode of injury and tympanic membrane perforation after three months (χ2 = 23.30; p = .00001). 13 Another study results also showed that there was statistically significant difference between TM perforation and age of the patient, severity of deafness, size of perforation (p <0.05) as shown. 8 Fazal I Wahid et al…”
Section: Discussionmentioning
confidence: 76%
“…As slap on the ear was more common resulting perforation at anterio-inferior quadrant of TM on left side hence there was statistically significant association between cause of trauma and site and side of perforation (x=24.13, p=0.020), (x=57.10.p=0.000), that is supported by study of Sannigrahi who found significant association between mode of injury and tympanic membrane perforation after three months (χ2 = 23.30; p = .00001) . 13 Another study results also showed that there was statistically significant difference between TM perforation and age of the patient, severity of deafness, size of perforation (p <0.05) as shown. 8…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations